Using federated machine learning to overcome the AI scale disadvantage : a promising new approach to training AI models lets companies with small data sets collaborate while safeguarding proprietary information - Bammens, Yannick; Hünermund, Paul (MIT Sloan Management Review, 2023)
Big Tech companies such as Google, Microsoft, and Amazon have an AI advantage thanks to the vast amounts of data that they collect through their respective platforms. Using federated machine learning (FedML) technology, companies with access to relatively small data sets can join forces in collaborative artificial intelligence projects while keeping proprietary data private. FedML could be a game changer in bridging the digital divide between organizations with and without big data.